Shoqar, Ibrahim. “The Elements of Islamic Educational Thought in Light of Changing Circumstances: An Analytical Look into the Factors of Self-Development,” Year 12, Issues 46-47 (Fall 1428 AH/ 2007 CE), Pp. 139-162. - شوقار, إبراهيم (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2007)
Ibrahim Shoqar’s article questions whether there is a balanced Islamic educational system that can keep pace with the changing reality in light of Islamic principles. It offers a unique contribution among a host of contributions that have discussed this question with the aim of identifying the best tools to restore the civilizational position of Islam among nations. Shoqar’s article provides an analytical study of the elements of educational thought in Islam aimed at shaping the features of contemporary Islamic educational philosophy in its quest to achieve the purpose of Islam’s universal message while finding qualified individuals to uphold this message. It also discusses the crisis of Islamic educational thought between the analytical/critical mindset and the insulated/constricting mindset (in an attempt to reconcile them), the philosophy of education from a doctrinal (ʿaqīdah) perspective, and elements of the philosophy of education in the age of globalization and an ever changing world.